Average Fracture Energy for Crack Propagation in Postfire Concrete. (30th November 2013) - Yu, Kequan; Yu, Jiangtao; Lu, Zhoudao
Abstract : Wedge-splitting tests of postfire concrete specimens were carried out in the present research to obtain the load-displacement curves. Ten temperatures varying from room temperature to 600°C were employed. In order to calculate the accurate fracture energy, the tails of load-displacement curves were best fitted using exponential and power functions. Three fracture energy quantities (fracture energy G F, stable fracture energy G FS, and unstable fracture energy G FU ) with their variation tendency and their mutual relationship were determined to predict energy consumption for the complete fracture propagation. Additionally, the stable fracture work W FS was also calculated. All these fracture parameters sustain an increase-decrease tendency which means that the fracture property of postfire concrete shares the same tendency.